2000
DOI: 10.4049/jimmunol.165.9.4917
|View full text |Cite
|
Sign up to set email alerts
|

A Subset of NKT Cells That Lacks the NK1.1 Marker, Expresses CD1d Molecules, and Autopresents the α-Galactosylceramide Antigen

Abstract: In the present report, we characterize a novel T cell subset that shares with the NKT cell lineage both CD1d-restriction and high reactivity in vivo and in vitro to the α-galactosylceramide (α-GalCer) glycolipid. These cells preferentially use the canonical Vα14-Jα281 TCR-α-chain and Vβ8 TCR-β segments, and are stimulated by α-GalCer in a CD1d-dependent fashion. However, in contrast to classical NKT cells, they lack the NK1.1 marker and express high surface levels of CD1d molecules. In addition, this NK1.1− CD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2001
2001
2008
2008

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 37 publications
1
31
0
Order By: Relevance
“…‫,ءء‬ Significant difference (p Ͻ 0.01) between the mAbϩGalϩBleo and GalϩBleo groups. cytokine production (9,10). In the present study, the protective effects of ␣-GalCer were not observed in J␣281 Ϫ/Ϫ mice.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…‫,ءء‬ Significant difference (p Ͻ 0.01) between the mAbϩGalϩBleo and GalϩBleo groups. cytokine production (9,10). In the present study, the protective effects of ␣-GalCer were not observed in J␣281 Ϫ/Ϫ mice.…”
Section: Discussionmentioning
confidence: 57%
“…Several studies have demonstrated that NKT cells participate in several immune and inflammatory responses because of their remarkable capacity to produce immunoregulatory cytokines such as IFN-␥ and IL-4 after stimulation with either anti-CD3 (7,8) or their glycolipid ligand (9,10).…”
Section: Treatment With ␣-Galactosylceramide Attenuates the Developmementioning
confidence: 99%
“…Recently, NK1.1 Ϫ T cells that bind CD1d tetramers have been detected in various tissues including the thymus, spleen, and lymph nodes (35), and our cultured NKT cells may represent these cells. A similar T cell subset was found to autopresent ␣-GalCer using CD1d on their own cell surface (40). Our NKT line also express CD1d, albeit at low level, and seem to autopresent ␣-GalCer as the cells are stimulated by the addition of ␣-GalCer without APCs (data not shown).…”
Section: Discussionmentioning
confidence: 77%
“…Although no increase in CD1d expression was observed on DP or APC subsets in the thymus or periphery, respectively, preliminary studies have found an increase in the expression of CD1d on the expanded NKT cell population in young B6.NZBc4L mice (our unpublished observations). It has been shown that CD1d-expressing NKT cells have the ability to autopresent ␣-galcer in the absence of APCs, raising the possibility that the expanded NKT cell population arises from autoactivation (41). Alternatively, altered T cell signaling may lead to the NKT cell expansion.…”
Section: Discussionmentioning
confidence: 99%